2013
DOI: 10.1111/ajo.12120
|View full text |Cite
|
Sign up to set email alerts
|

Emergency obstetric simulation training: How do we know where we are going, if we don't know where we have been?

Abstract: Evidence exists for a positive impact of training in obstetric emergencies, although the majority of the available evidence applies to evaluation at the level of participants' confidence, knowledge or skills rather than at the level of impact on clinical outcomes. The model of simulation-based training is an appropriate one for the Australian setting and should be further utilised in rural and remote settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 58 publications
0
32
0
8
Order By: Relevance
“…The current evidence base suggests the use of local, inter-professional, in situ training provided to all staff in maternity care units. [5][6][7] Simulation training has been recognised as a valuable tool to improve not only knowledge and clinical skills, but also to improve communication and teamwork during the management of obstetric emergencies, and has been shown to lead to improved perinatal outcomes. [8][9][10] In-house training in particular is associated with improved outcomes 5 and the utilisation of training in remote and rural sites is an issue with obvious relevance to the Australian healthcare paradigm.…”
Section: Resultsmentioning
confidence: 99%
“…The current evidence base suggests the use of local, inter-professional, in situ training provided to all staff in maternity care units. [5][6][7] Simulation training has been recognised as a valuable tool to improve not only knowledge and clinical skills, but also to improve communication and teamwork during the management of obstetric emergencies, and has been shown to lead to improved perinatal outcomes. [8][9][10] In-house training in particular is associated with improved outcomes 5 and the utilisation of training in remote and rural sites is an issue with obvious relevance to the Australian healthcare paradigm.…”
Section: Resultsmentioning
confidence: 99%
“…These themes have been reiterated in two more recent reviews for obstetric training [14,23], one of which concluded that all maternity and neonatal health professionals should attend in-service training sessions. Furthermore, on-site 'in-house' training with low-tech, highly realistic models is more readily implementable than off-site training at simulation centres, and training integrated into institutional clinical governance and quality-improvement initiatives is likely to have better results.…”
Section: Myth 1: Training Must Be Effectivementioning
confidence: 99%
“…There is proof of principle that some training for obstetric emergencies is associated with improvements in outcome [14, 23,34,47]. However, there is a dearth of data on the effect of local context.…”
Section: Myth 3: Training Is Independent Of Contextmentioning
confidence: 99%
“…The demonstration of improvement in clinical outcomes following simulation based training is an essential endeavour and a challenging one [15]. The assumption is frequently made that training using mannequins will improve delivery skills, translating into improved outcomes for mothers and babies [16].…”
Section: Discussionmentioning
confidence: 99%